2021
DOI: 10.1177/1066896920988348
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Subtypes and PD-L1 Expression in Primary Urethral Adenocarcinoma: A Series of 5 Cases

Abstract: Background and Objectives Urethral adenocarcinoma is a rare disease with poor prognosis that can display multiple histologic patterns and has an unclear histogenesis. Radical surgery with extensive periurethral resection is the preferred therapeutic approach. Both chemotherapy and radiotherapy have been used as complementary treatment options. Due to the tendency of these tumors to recur, treatment-associated complications, and the limited choice of therapeutic options, patient management can be difficult. Giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A search of the literature showed that there are few data on the detection of PD-L1 or the use of PD-L1 inhibitors in primary urethral cancer. 21,22 Antigen-presenting cells, such as human monocytes, as well as activated human and murine dendritic cells, express PD-L1. 23 PD-1 inhibitors mainly act on PD-1 inhibitor molecules on the T cell membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A search of the literature showed that there are few data on the detection of PD-L1 or the use of PD-L1 inhibitors in primary urethral cancer. 21,22 Antigen-presenting cells, such as human monocytes, as well as activated human and murine dendritic cells, express PD-L1. 23 PD-1 inhibitors mainly act on PD-1 inhibitor molecules on the T cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…A search of the literature showed that there are few data on the detection of PD-L1 or the use of PD-L1 inhibitors in primary urethral cancer. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the patient refused the chemotherapy because of adverse reactions including severe systemic edema, hand and foot skin peeling, and lower extremity venous thrombosis. Recent study found that some urethral adenocarcinomas may strongly express PD-L1 and thus could potentially allow the use of immunotherapy in selected cases of advanced or recurrent adenocarcinoma [13]. We wonder if the immune checkpoint inhibitor is working for this patient.…”
Section: Discussionmentioning
confidence: 99%